2015
DOI: 10.7554/elife.07938
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between PRMT1-mediated methylation and ubiquitylation on RBM15 controls RNA splicing

Abstract: RBM15, an RNA binding protein, determines cell-fate specification of many tissues including blood. We demonstrate that RBM15 is methylated by protein arginine methyltransferase 1 (PRMT1) at residue R578, leading to its degradation via ubiquitylation by an E3 ligase (CNOT4). Overexpression of PRMT1 in acute megakaryocytic leukemia cell lines blocks megakaryocyte terminal differentiation by downregulation of RBM15 protein level. Restoring RBM15 protein level rescues megakaryocyte terminal differentiation blocked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(151 citation statements)
references
References 100 publications
(124 reference statements)
4
128
0
Order By: Relevance
“…The present study demonstrated that DB75 rescues PRMT1-blocked MK differentiation via promoting RBM15 expression. Our previous data indicated that PRMT1 methylates RBM15 at R578 and promotes RBM15 protein level degradation via ubiquitylation in a leukemia cell line (8). The present study also suggested that PRMT1 reduces RBM15 expression in human stem cells, which may contribute to defective megakaryopoiesis.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The present study demonstrated that DB75 rescues PRMT1-blocked MK differentiation via promoting RBM15 expression. Our previous data indicated that PRMT1 methylates RBM15 at R578 and promotes RBM15 protein level degradation via ubiquitylation in a leukemia cell line (8). The present study also suggested that PRMT1 reduces RBM15 expression in human stem cells, which may contribute to defective megakaryopoiesis.…”
Section: Discussionmentioning
confidence: 50%
“…Therefore, PRMT1-mediated MK blockage may contribute to leukemogenesis. PRMT1 promotes the production of MK-erythroid progenitor cells; however, PRMT1 has to be turned off to generate mature, polyploidy CD41 + CD42 + MK cells (8). The present study demonstrated that PRMT1 negatively modulated differentiation toward the megakaryocytic lineage in human CD34 + hematopoietic cells.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…At this point, it is not clear what arginine residues within CIITA are targeted by PRMT1. In addition, it remains undetermined whether PRMT1-induced CIITA degradation is solely a result of PRMT1-dependent arginine methylation or a secondary effect contingent on communications with other types of post-translational modifications since PRMT1-dependent arginine methylation has been shown to form crosstalk with acetylation2627, ubiquitination2829, and phosphorylation3031. It has been previously shown that CIITA poly-ubiquitination plays a role in regulating its stability20, although CIITA mono-ubiquitination could enhance its activity without altering its half-life32.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 16 , a close structural analogue of DB75, was used as a tool compound to inhibit PRMT1-mediated Smad6 methylation, revealing that the methyltransferase activity of PRMT1 is essential for bone morphogenetic proteins (BMP)-induced Smad1/Smad5 phosphorylation and downstream signaling activation [123]. Recently, we found that DB75 inhibits PRMT1-mediated putative RNA-binding protein 15 (RBM15) methylation at residue R578 [124]. Arginine methylation of RBM15 leads to its ubiquitination by the E3 ligase CNOT4 and subsequent degradation.…”
Section: Prmt1-specific Inhibitorsmentioning
confidence: 99%